Penyuluhan Literasi Keuangan Bagi UMKM Jamu Gendong - Herlina, Herlina; Melina, Erny; Sitanggang, Prayetno Agustinus; Luthfi, Musthafa; Wahab, Abdul (Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this community service activity (PKM) is to increase the knowledge about financial literacy for Mbak Eka's business herbal medicine (UMKM jamu gendong) so that it can be used in business development. The methods that used in this community service activity are giving a lecture and discussions. The stages start from coordinating with business owners, provide counseling and the evaluation stage. The discussion shows that business owner’s has been in the financial literacy level, namely sufficient literate, meaning that they already have knowledge and confidence of financial service institution and have existing financial products. Mbak eka as the owner of the business has known about the procedures to obtaining additional business capital from banks and also the risk. However, mbak eka doesn’t taking the advantage of these capital financial services because she doesn’t need it yet. The Business owners also have has the budgeting skills and saving habits. However, the savings only for consumption and not used for investment. The hoped that the business owner will be able to develop financial strategies through investment skills in the form of being able to allocate savings, from selling herbal medicine to business capital in order to transition from conventional marketing to online marketing in order to reach a wider market.